Insect Biodiversity in Mangrove Area of Tatengesan Village, Pusomaen District in Southeast Minahasa, North Sulawesi - Feby Febrianty Toding Rante; Yermia Semuel Mokosuli; Iriani Setyawati; Ferny Margo Tumbel; Helen Joan Lawalata (Advances in Tropical Biodiversity and Environmental Sciences, 2023)
The existence of insects cannot be separated from the condition of their habitat. The mangrove area of ​​Tatengesan Village is one of the ecotourism site in Minahasa, North Sulawesi, that can support the survival of insects. This study aimed to determine the distribution and diversity of insects and the factors that influence the insect diversity in the mangrove area. The type of research used is descriptive quantitative research by conducting data collection activities, analyzing data and interpreting data with the aim of making a description of the events that occurred. The animals were exploratory collected by using insect nets (sweep net), beating cloth (beating), and bare hands (hand collecting). The results showed that there were 1225 individual insects consisting of 14 insect species, which were divided into 14 genera, 11 families and 6 orders of insects. The insect diversity index value was 0.27 which was classified as low. The dominance index value was 0.90 which was classified as high. The evenness index value was 0.10 which was classified as low.